Spinoza e a Igualdade da Mulher - Gullan-Whur, Margareth; Araújo, Antonia Dilamar; Kessy, Marsana; Fragoso, Emanuel Angelo da Rocha (Revista Conatus - Filosofia de Spinoza (ISSN 1981-7509), 2021)
Texto publicado originalmente em Theoria (Filosofoska institutionen, Kungshuset Lundagård, Lund, Suede, ISSN 0040-5825), no vol. 68, no 2, 2002, pp. 91-111. Reprint by permission of the publisher and the author.